2002
DOI: 10.1614/0043-1745(2002)050[0157:iotarh]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Influence of temperature and relative humidity on the foliar activity of mesotrione

Abstract: Greenhouse studies were conducted to examine the influence of temperature and relative humidity (RH) on the foliar activity of mesotrione on five weed species. Regression analysis was performed allowing for comparison of estimated GR50 (herbicide dose to inhibit growth by 50%) values for each weed response at either temperature (18 or 32 C) or RH level (30 or 85%). Temperature and relative humidity did not influence the response of ivyleaf morningglory, common cocklebur, and velvetleaf to mesotrione markedly. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
86
0
6

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(100 citation statements)
references
References 14 publications
8
86
0
6
Order By: Relevance
“…Moreover, this study showed greater biomass reduction under warm conditions for the mixtures 2.4-D+dicamba and 2.4-D+florasu-lam. These results are in agreement with the previous reports describing higher herbicide activity under high temperature conditions compared to low temperature [5,16,17]. In contrast to temperature, relative humidity did not influence weed response to herbicide stress.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Moreover, this study showed greater biomass reduction under warm conditions for the mixtures 2.4-D+dicamba and 2.4-D+florasu-lam. These results are in agreement with the previous reports describing higher herbicide activity under high temperature conditions compared to low temperature [5,16,17]. In contrast to temperature, relative humidity did not influence weed response to herbicide stress.…”
Section: Discussionsupporting
confidence: 93%
“…It resulted in significantly smaller biomass reduction when both weed species were kept at low temperature in comparison with high temperature, while the mixture of 2.4-D with florasulam caused differences only when it was used against P. rhoeas. This agrees with the results obtained by C o e t z e r et al [4] as well as J o h n s o n and Y o u n g [16] who reported that particular weed species responded to herbicides applied under variable temperature regimes differently or some of them were not temperature dependent. Moreover, this study showed greater biomass reduction under warm conditions for the mixtures 2.4-D+dicamba and 2.4-D+florasu-lam.…”
Section: Discussionsupporting
confidence: 92%
“…As espécies de plantas suscetíveis ao mesotrione apresentam sintomas de amarelecimento nas folhas aos três dias após a aplicação (DAA), com posterior branqueamento, que progridem para a necrose e morte da planta em até duas semanas. Os sintomas se desenvolvem mais rapidamente na presença de luz (Pallet et al, 1998;Wichert et al, 1999;Johnson & Young, 2002) O mesotrione causa em algumas variedades ou híbrido de milho sintomas de fitointoxicação, porém isso não resulta em perdas na produtividade de grãos (Furtado, 2004;Masiunas et al, 2004). O milho é tolerante ao mesotrione, provavelmente, devido à capacidade de desativação do princípio ativo e à translocação para compartimentos celulares -vacúolo e meio extracelular (Mitchell et al, 2001;Johnson & Young, 2002;O´Sullivan et al, 2002).…”
Section: Introductionunclassified
“…As espécies de plantas suscetíveis ao mesotrione começam a apresentar sintomas de amarelecimento das folhas aos três dias após a aplicação (DAA), com posterior branqueamento das folhas, progredindo para a necrose e morte em até duas semanas (Pallet, 2000;Johnson & Young, 2002). Em alguns híbridos de milho mais sensíveis, o mesotrione tem provocado leve fitointoxicação, porém não foram observadas perdas na produtividade de grãos (O'Sullivan et al, 2002;Masiunas et al, 2004).…”
Section: Introductionunclassified